2012
DOI: 10.1002/jctb.3894
|View full text |Cite
|
Sign up to set email alerts
|

Economic production of Bacillus subtilis SPB1 biosurfactant using local agro‐industrial wastes and its application in enhancing solubility of diesel

Abstract: BACKGROUND: The present work aimed to optimize a new economic medium for lipopeptide biosurfactant production by Bacillus subtilis SPB1 for application in the environmental field as an enhancer of diesel solubility. Statistical experimental designs and response surface methodology were employed to optimize the medium components. RESULTS: A central composite design was applied to increase the production yield and predict the optimal values of the selected factors. An optimal medium, for biosurfactant production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
5
36
0
Order By: Relevance
“…This result is in very close agreement with the findings of Huszcza and Burczyk [29], who reported that the biosurfactant activity produced by B. coagulans was enhanced with the addition of salts. In addition, the maximum activity of the biosurfactant produced by B. subtilis was achieved with the addition of 15% NaCl [30]. The current results also indicated that B. salmalaya can grow under conditions of high salinity.…”
Section: Resultsmentioning
confidence: 56%
“…This result is in very close agreement with the findings of Huszcza and Burczyk [29], who reported that the biosurfactant activity produced by B. coagulans was enhanced with the addition of salts. In addition, the maximum activity of the biosurfactant produced by B. subtilis was achieved with the addition of 15% NaCl [30]. The current results also indicated that B. salmalaya can grow under conditions of high salinity.…”
Section: Resultsmentioning
confidence: 56%
“…This suggests the competence of B. subtilis biosurfactant in promoting methyl orange treatment by A. veronii GRI. SPB1-derived , +0.15 % biosurfactant biosurfactant has been previously described as enhancer of diesel solubility and mobility (Mnif et al 2012b(Mnif et al , 2013. In another study, in situ SPB1 biosurfactant production (Mnif et al 2014) and ex situ SPB1 biosurfactant addition were reported to enhance hydrocarbon assimilation .…”
Section: Effect Of Ph On Decolorization Efficiencymentioning
confidence: 96%
“…A variety of cheap raw materials, including plant-derived oils, oil wastes, starchy substances, lactic whey and distillery wastes have been reported to support biosurfactant production. Previous studies reported the use of rice bran [54], soy bean flour [55,56], soybean curd residue [57], potato process effluents [55], potato peels [58,59], sesame peel flour [60], orange peels [61], millet flour [62] tuna fish flour [59], molasses and whey [63], tuna fish cooking residue [60] and soybean sauce [64] for lipopeptide production. Also, numerous studies reported the production of lipopeptide using cassava wastewater as substrate [65][66][67].…”
Section: Use Of Low-cost Raw Materialsmentioning
confidence: 99%